Sportdate för mobila enheter - JOHANSSON, KRISTOFFER (My University, 2018)
Sportdate is an online meeting place for people with an interest in health and fitness. The web service is run by the two companies Sportdate AB and SoftIT AB. Previously, access to the service has been provided through a traditional and a mobile website. For mobile device users, this has meant that no automatic authentication is offered. You also have not been able to receive information using the mobile platform's notification system. The existing system also limits the possibilities of introducing a new type of functionality that utilizes the mobile device's GPS receiver. To solve the issues with the existing system and offer an improved user experience, a mobile application has been developed. The application is designed in such a way that it allows sharing of information with the mobile site to facilitate the maintenance of the two subsystems. Originally, this project was intended to include the development of an application for both of these platforms, but quite early during the work, it became apparent that this would not be possible within the timeframe for the project, it was then decided that this project would prioritize the completion of the application for iOS. This report, therefore, focuses exclusively on application development for this platform. With the exception of a few days working at the client's office, most of the work on the project was carried out remotely. The iOS application that was completed during the project is available today on the App Store, Apple's Marketplace for Applications under the name ”Sportdate".
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science